P1-S6.25 The male reproductive health project: using research-based interventions to increase male clients and STI testing at family planning clinics. (10th July 2011) - Fine, D; Goldenkranz, S; Adamian, J; Ranjan, S; Pan, A; Baker, J; Rink, E; Tran, N; Johnson, D; Carlon, A
Abstract : Background: Women comprise >95% of US family planning (FP) clinic clients. The Male Reproductive Health Project (2008–2013) is a national research demonstration effort implementing empirically-based interventions to increase male FP clients and male testing for sexually transmitted infections (STI). Methods: In 2009 interventions at 5 FP grantees included: male outreach via FP clinics' female clients and other agencies serving men, clinic efficiency assessments, FP staff training, and modifying clinic environments. Study population currently includes male FP client visit records (2004–2009) from 2 grantees. In separate analyses for Montana (MT) (2891 visits) and San Diego (SD) (7008 visits) grantees we analysed chlamydia (CT) testing (urine/NAAT) and positivity (CT+) by clinic, age, race/ethnicity, intervention status (pre: 2004–2008; post: 2009), insurance status, new/returning client, and federal Title X FP funding. Multivariate models developed. Results: MT-67% of visits aged 20–29 y; 94% non-Hispanic whites. Annual visits increased 60%--pre-intervention (2004–2008) x̄ =438 visits/y; post (2009)=702 visits. CT testing increased 44% (2004–2008 x̄ =58% of visits/y tested; 2009: 78% tested). Significant (p<0.05) multivariate factors related to CT testing: intervention status (AOR=2.21), racial/ethnic minority (AOR=2.06), new client (AOR=5.59), visit's federal funding (AOR=3.04), and clinic (Billings: AOR=0.45). CT+ was 13.9%. Factors related to CT+: age<20 y (AOR=2.44, Ref:>29 y), no insurance (AOR=1.67), and federal funding (AOR=1.76). Annual female FP clients were stable (2004–2008: 5085/y; 2009: 5650). SD-43% of visits aged 20–29 y; 66% Hispanic. Annual visits increased 18%--pre-intervention x̄ =1045/y; post=1235 visits. CT testing increased 41% (pre: x̄ =29% of visits/y tested; post: 41% tested). Factors related to testing: new client (AOR=2.39) and intervention status (AO=1.76). CT+ was 6.4%. Factors related to CT+: age<20 y (AOR=3.13), black race (AOR=2.29), new client (AOR=2.47), and clinic (Beach: AOR=0.40). Annual female FP clients were stable (2004–2008: 4440/y; 2009: 4833). Conclusions: Early data indicate FP clinic interventions significantly increased male clients and the proportion tested for CT without reducing female FP clients. Screening prioritised new male patients. Like other CT programs, young and minority males have increased infection risk. CT positivity varied by clinic, supporting use of local data to inform male STI services at FP clinics.